Extraction therapy in patients with class II/2 malocclusion = Extraktionstherapie bei Patienten mit einer Angle-Klasse II/2 - Stellzig-Eisenhauer, Angelika; Basdra, Efthimia K.; Kube, Christian; Komposch, Gerda (Journal of orofacial orthopedics, 1999)
The aim of this study was to analyze the dynamic development of Class II, Division 2 malocclusion with reference to the untreated patients from the Belfast Growth Study. As a second step, the influences of premolar extraction in all 4 quadrants and of maxillary second molar extraction in the upper jaw in Class II/2 patients were examined, focusing on the cephalometric variables in comparison to those of the untreated patients from the Belfast study. The longitudinal cephalometric values of 20 patients in each group were compared.